The Role of Oxidative Stress and Antioxidant Balance in Pregnancy. (27th September 2021) - Hussain, Tarique; Murtaza, Ghulam; Metwally, Elsayed; Kalhoro, Dildar Hussain; Kalhoro, Muhammad Saleem; Rahu, Baban Ali; Sahito, Raja Ghazanfar Ali; Yin, Yulong; Yang, Huansheng; Chughtai, Muhammad Ismail; Tan, Bie
Abstract : It has been widely known that oxidative stress disrupts the balance between reactive oxygen species (ROS) and the antioxidant system in the body. During pregnancy, the physiological generation of ROS is involved in a variety of developmental processes ranging from oocyte maturation to luteolysis and embryo implantation. While abnormal overproduction of ROS disrupts these processes resulting in reproductive failure. In addition, excessive oxidative stress impairs maternal and placental functions and eventually results in fetal loss, IUGR, and gestational diabetes mellitus. Although some oxidative stress is inevitable during pregnancy, a balancing act between oxidant and antioxidant production is necessary at different stages of the pregnancy. The review aims to highlight the importance of maintaining oxidative and antioxidant balance throughout pregnancy. Furthermore, we highlight the role of oxidative stress in pregnancy-related diseases.